Treatment planning system dose verification for MLC-shaped photon beams in postal radiotherapy dosimetry audit: a single-centre pilot study - Muhammad Safwan Ahmad Fadzil; Rohaizah Mohamad @ Ab Rahim; Nor Aniza Azmi; Akmal Sabarudin; Abdul Khaliq Mohd Saparudin; Mohd Taufik Dollah; Ung Ngie Min; Noramaliza Mohd Noor (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study aimed to initiate the fourth consecutive phase of remote dosimetry auditing by the International Atomic Energy Agency (IAEA) for radiotherapy facility in Malaysia, which focuses on the validation of the treatment planning system (TPS) doses for photon beams shaped using multileaf collimators (MLC). Thermoluminescence dosimeter (TLD-100), encased within plastic capsules, were dispatched to the radiotherapy centre along with an IAEA TLD holder, irradiation datasheets, and technical instructional booklet. The irradiation setup involved exposing the TLD-100 to assess dose variations concerning field size and configuration across a range of MLC shaped segments, encompassing both regular and irregular geometries, including wedged fields. Each capsule received an irradiation dose of 2 Gy using 6- and 10 MV photon beams. A comparison was made between the dose calculated by the TPS (DTPS) and the doses measured by both the ionization chamber (DIC) and TLD-100 (DTLD). No deviations exceeding ±5% of all measurements over DTPS were observed. The mean ratios were 1.007 ± 0.014 and 1.003 ± 0.004 for DIC/DTPS with 6- and 10 MV beams, respectively, while DTLD/DTPS recorded mean ratios of 1.023 ± 0.007 for 6 MV and 1.009 ± 0.022 for 10 MV beams. This project marks the successful initiation of dose verification for the TPS in accordance with IAEA guidelines, enabling the assessment of dosimetric data related to the use of MLC. A recommendation was put forth to expand the scope of the postal dosimetry audit at the national level, with the goal of improving radiotherapy treatment dose precision.